A new and unusually ornate southern African dung beetle species in d’Orbigny’s Onthophagus Group 18 (Coleoptera: Scarabaeidae: Onthophagini) - Deschodt, Christian M.; Sole, Catherine L. (Zootaxa, 2024)
Onthophagus pragtig Deschodt, new species is described and illustrated from South Africa. Its known collection localities are shown. We also briefly describe and illustrate three distinct subgroups in the18th Onthophagus group of d’Orbigny (1913) and further provide a checklist of the known species in this group while dividing them into these subgroups where known.